The Risks of Polymethyl Methacrylate: An Integrative Review of 587 Complication Reports - Sampaio, Marcelo Moura Costa; Costa, Alessandra Lima; Vianna, Luiz Henrique Megale Conteville; Marinho, Pedro Burlacchini Sanches; Santos, Ionara Maria de Almeida; Moraes, Mariana Alcantara Rodrigues de (Revista Brasileira de Cirurgia Plástica (RBCP) – Brazilian Journal of Plastic Surgery, 2024)
Introduction The demand for minimally-invasive esthetic procedures has boosted the use of polymethyl methacrylate (PMMA) as a dermal filler, which was initially approved for human immunodeficiency virus (HIV)-related lipodystrophies. Improper PMMA use can lead to severe complications, including inflammation, material migration, infections, and systemic repercussions. The present review investigated PMMA-related risks and complications reported in the literature over the past 20 years.Materials and Methods We conducted an integrative review of descriptive studies on PMMA complications published from 2004 to 2024 and retrieved from PubMed, Scientific Electronic Library Online (SciELO), and Scopus. We analyzed 38 studies, encompassing 587 cases, and excluded articles published outside the specified period and those not meeting the inclusion criteria.Results We identified 587 cases of PMMA-related complications, 64% of them occurring in Brazil. The most common complication site was the malar region, followed by the nasolabial fold, the gluteal area, and the lips. The complications ranged from immediate to delayed, and from mild to severe. The most frequent complications included erythema (26%), pruritus (16%), edema (11%), granulomas (21%), nodules (14%), and skin changes (8%). Severe cases included renal failure, hypercalcemia, septic shock, infections, and tissue necrosis. The volume injected ranged from 1.9 to 900 mL. The treatment predominantly involved steroids, antibiotics, and surgical interventions, including excisions, abscess drainage, and debridement.Conclusion The use of PMMA fillers may lead to severe complications, often unrelated to the correction of HIV-related lipodystrophies; PMMA presents significant risks, including systemic complications, requiring surgical removal.
Keywords: case reports; dermal fillers; polymethyl methacrylate; review; risk